Effect of Egg Disinfection by Silver Nanoparticles on Eggshell Microbial Load, Hatchability and Post-hatch Performance of Quail Chicks - Ibrahim, Faten A.; El.Mousafa , Kout Elkloub M.; El Sabry, M.I.; Badr, Jihan M.; Hassan, A.S.I. (International Journal of Poultry Science, 2018)
Background and Objective: Sanitation improvement of fertile eggs is an important point of research, as it is the goal of selection of the hygiene programs in commercial hatcheries. Silver nanoparticles (Ag-NPs) have new physical and chemical characteristics enabling it to have a strong antibacterial activity. This study was aimed to evaluate the effect of different concentrations of Ag-NPs as a disinfectant, on a microbial load on the quail eggshell, embryonic mortality, hatchability, chick quality and post-hatch performance. Methodology: Silver nanoparticles were synthesized and characterized by UV, concentration and transmission electron microscopy (TEM). A total of 1920 fertile quail eggs were randomly divided into 4 treatment groups, one control group disinfected by spraying with a commercial disinfectant (TH4) and three treated groups sprayed with 30, 40 or 50 ppm of Ag-NPs. Thirty minutes after spraying, eggs in each group were sampled for determination of total bacterial and total coliform counts. Results: Results showed that bacterial loads on the eggshell were declined with the elevation of the concentration of Ag-NPs used. The 50 ppm concentration of Ag-NPs had the lowest bacterial load. Also, hatchability of the treated groups was increased by increasing Ag-NPs concentration. Hatchability of Ag-NPs 50 group was higher than the control group (p